An analysis on child marriage in Malaysia: special reference to law reform (Marriage & Divorce) Act 1976 / Nurazie Izyani Samsudin ... [et al.] - Samsudin, Nurazie Izyani; Anuar, Nurliyana; Lufti, Nabilah; Khazali, Farim Shahnan (Faculty of Law, 2013)
This research is conducted for the purpose of highlighting the issues and problems concerning child marriage in Malaysia. Besides that, the research is also conducted to analyze the law in Malaysia which is Law Reform (Marriage & Divorce) Act 19 and international conventions regarding child marriage. Next, in this research also analyze the perspective of international views by scrutinizing the examples from other countries (Bangladesh, Nepal, India and United States of America). This research is conducted through library research as primary and secondary sources as well as online sources. This research is to provide guidelines, recommendations and suggestions for the supplement to the existing law in Malaysia. Plus, this research is also to give a great impact for the protection for the rights and welfare of the children.